Transcription Initiation From Within P Elements Generates Hypomorphic Mutations in Drosophila melanogaster. - Lafave, M.C.; Sekelsky, J. (Genetics, 2011)
Numerous transposable element insertions in Drosophila melanogaster cause hypomorphic mutations. We report that transcription initiation within a region found in many P-element constructs provides an explanation for why some gene function is retained. We detected evidence of this transcription in four different types of P constructs, regardless of whether the insertion was in a coding exon, intron, 5' untranslated region, or upstream of the gene span.